Collaborative Governance in the Management of the Nongsa Special Economic Zone (SEZ), Batam City - Nugraha, Lyona Ayu; Samin, Rumzi; Septiawan, Armauliza (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The development of the Nongsa Special Economic Zone (SEZ) in Batam City is aimed at becoming a strategic hub for digital economy growth and creative industries. However, its implementation faces serious governance challenges, such as overlapping authority between the Batam City Government and the Batam Indonesia Free Zone Authority (BP Batam), inadequate supporting infrastructure, and low stakeholder engagement. This study aims to analyze the collaborative governance model in the management of the Nongsa SEZ using the framework of Ansell and Gash, which consists of four core components: starting conditions, institutional design, facilitative leadership, and the collaborative process. This research employs a qualitative approach with a case study method, utilizing in-depth interviews, document analysis, and participatory observation as data collection techniques. The findings reveal four main issues: power imbalances, exclusivity in institutional design, weak facilitative leadership, and suboptimal collaborative processes. These factors hinder the development of inclusive and sustainable collaboration. This study offers practical contributions by proposing a participatory collaborative forum and academic contributions by enriching the literature on collaborative governance in digital economy-oriented SEZ development in Indonesia. This study concludes that the governance of the Nongsa SEZ has not yet fully met the prerequisites for effective collaboration as defined by Ansell and Gash. Strengthening formal collaborative forums, enhancing the capacity of local actors, and aligning regulations across government levels are necessary to support participatory, integrated, and sustainable SEZ governance.